Pray the Lord’s Prayer well - González Faus, José Ignacio (Razón y fe, 2021)
The fifth petition of the Lord’s Prayer uses a verb in Greek that does not mean to forgive (as we recite), but to let go. This seems to be because, in Aramaic, the same word means sin and debt. Men usually think that sins can be atoned for or forgiven but debts “must be paid”. In a society flooded with debts (as was Jesus’ and is ours), this places the insolvent debtor totally at the mercy of the creditor. The conception of sin as a debt contracted before God helps us to understand the gratuitousness of forgiveness and obliges us, when we are creditors, to mercy towards the insolvent debtor. This has serious social consequences.
Keywords: offense; debt; sin; contraction; liberation